Uji Beberapa Dosis Pupuk Hayati Mikoriza Terhadap Pertumbuhan Stum Mini Karet (Hevea brasiliensis) - Elisa Sianipar, Sudnoris Sulvana; Saputra, Sukemi Indra; Puspita, Fifi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Rubber (Hevea brasiliensis) is plantation crop commodity widely cultivated in Indonesia especially Riau. To increase rubber production must be do replanting. The research aimed examine the effect some dose of mycorrhizal biofertilizer on the growth of rubber mini stump and get better dose. Research carried out at screen house in the Technical Services Unit Faculty of Agriculture in August until November 2013. Research used Completely Randomized Design (CRD) with       5 treatment dose of mycorrhizal biofertilizer and 4 replication, each experimental contained 3 rubber mini stump and 2 as sample. The parameters measured were high accretion seedling (cm), the number accretion of leaves (sheet), stem accretion of diameter (mm), seedling root volume (ml), dry weight of root (g), shoot root ratio (g) and the percentage of infected mycorrhizal root (%). The result showed some dose mycorrhizal biofertilizer significant on the percentage of infected mycorrhizal root and non significant of high accretion seedling, the number accretion of leaves, stem accretion of diameter, seedling root volume, dry weight of root and shoot root ratio.   Keywords : Mycorrhizal biofertilizer, dose, rubber mini stump.